URGENSI IINTEGRASI NILAI LOCAL WISDOM DALAM KONFLIK SUPORTER SEPAKBOLA - Pujiyono, Pujiyono; Mulyanto, Mulyanto (Faculty of Law, Universitas Sebelas Maret, 2014)
AbstractThis study was conducted to describe the factors that cause conflict among football fans. There are findings of two (2) factors causing conflict football supporters that internal factors are derived from the self-supporters and external factors outside themselves supporters as unfair referee; conditions of players, and conditions in the field as revenge of the past, the movement spontaneous, mutual blasphemy and provocateur. In an academic perspective, need to be developed integrating the values of local wisdom in preventing conflict between supporters of football, including the proverbial “win without ngasorake”. If supporters uphold these values , conflict and reduced football fans are increasingly aware of the importance of maintaining fair play. AbstrakPenelitian ini dilakukan untuk menjelaskan faktor-faktor yang menyebabkan konflik antar suporter sepakbola. Ada temuan terdapat 2 (dua) faktor penyebab konflik supporter sepak bola yakni faktor internal yang berasal dari dalam diri supporter dan faktor eksternal yang berasal dari luar diri supporter seperti Wasit yang tidak adil; Kondisi pemain; dan Kondisi di lapangan seperti dendam masa lalu, gerakan spontan, saling hujat dan provokator. Dalam perspektif akademis, perlu dikembangkan pengintegrasian nilai-nilai local wisdom dalam mencegah konflik antar suporter sepakbola, diantaranya pepatah “menang tanpa ngasorake”. Apabila suporter menjunjung tinggi nilai tersebut, konflik suporter sepakbola berkurang dan semakin sadar pentingnya menjaga fair play.